Special physical preparation of skilled wrestlers during a macrocycle in the conditions of higher educational establishment. - Ogar' G.O; Sancharov V.A; Lasitsa V. I. (Kharkov National Pedagogical University, 2010)
It is developed and experimentally grounded efficiency and methods of improvement of the special physical preparedness of skilled fighters. It is certain that a method parts on a few stages of preparation of training macrocycle and optimized for sportsmen which parallel study in higher educational establishment. It is set that the educational training process of skilled fighters must take into account the specific of organization of educational process of educational establishment and answer the calendar of competitions on a CY.